Developing Ethnomathematics-Based Worksheets for Junior High School: A Research and Development Approach - Anggun Badu Kusuma; Anton Jaelani; Arifin Suryo Nugroho (EduMa: Mathematics education learning and teaching, 2025)
Worksheets are frequently utilized as educational tools to assist teachers in learning. Integrating ethnomathematics into lessons enhances the significance of mathematics education. This study aims to develop ethnomathematics-based worksheets for junior high school students. The research employs a research and development methodology, following the stages of defining, designing, and developing as outlined by Thiagarajan. The participants include material experts, media experts, teachers, and junior high school students. The findings indicate that the worksheets are valid and suitable for further research. Feedback from teachers and students suggests that the worksheets are practical and effective. Observations from limited trials show that students and teachers are enthusiastic about learning.